Syekh Nawawi Al Bantani: Pemikirannya Tentang Pendidikan dan Relevansinya Dengan Pendidikan Islam Kontemporer - Mahmudi, Fajar Al; Bungsu, Agung Pangeran (STAI Darul Qalam Tangerang, 2024)
This research seeks to study and explore the thoughts of one of the great Islamic scholars from Indonesia, Sheikh Nawawi Al Bantani. His works and thoughts on Islamic education are still being studied to improve and develop Islamic education in Indonesia. Among his thoughts that can be relevant is strengthening the formation of students' character to face the development of the times and the advancement of science and technology. This research is included in the type of library research by using a descriptive analysis approach to describe the real situation that is currently occurring, then the collected data is then processed according to existing procedures. So as to produce the idea of Sheikh Nawawi's thoughts that are useful and can be used, especially in the world of Islamic education in an effort to shape the character of students. The results of the study show that overall almost all aspects of Islamic educational thought initiated by Sheikh Nawawi focus on character building. So that his thoughts are very relevant to be used today to face the flow of globalization and the advancement of science and technology